The Employment and Wage Effects of Oil Price Changes : A Sectoral Analysis - Keane, Michael (IMF Working Papers; Working Paper ;, 1995)
In this paper, we use micro panel data to examine the effects of oil price changes on employment and real wages, at the aggregate and industry levels. We also measure differences in the employment and wage responses for workers differentiated on the basis of skill level. We find that oil price increases result in a substantial decline in real wages for all workers, but raise the relative wage of skilled workers. The use of panel data econometric techniques to control for unobserved heterogeneity is essential to uncover this result, which is completely hidden in OLS estimates. We find that changes in oil prices induce changes in employment shares and relative wages across industries. However, we find little evidence that oil price changes cause labor to consistently flow into those sectors with relative wage increases.